A folded ice monolayer. Issue 36 (10th September 2020) - Xu, Ying; Xuan, Xiaoyu; Zhang, Zhuhua; Guo, Wanlin
Abstract : A folded ice with high stability is predicted by means of a novel tiling method augmented with ab initio calculations. Abstract : A highly stable ice monolayer with folded structural motifs is predicted by means of a novel tiling method augmented with ab initio calculations. This ice monolayer has every two neighboring water hexamers connected by a water square yet folded into two distinct planes, and is thus coined as a folded ice model. It is in the ground state in a range of water densities from 0.08 to 0.12 Å −2, with a stronger energy preference at a lower water density. Its stability shown by ab initio molecular dynamics simulations can sustain up to a temperature of 100 K. The tiling method also enables the prediction of a family of considerably stable ice monolayers with a variety of puckered structures. These results enrich our knowledge of low-dimensional water structures and pave a way to explore more exotic ice nanostructures under confinements.